Analysis of the Effect of HDI, Foreign Investment, Domestic Investment and Population Projections on Economic Growth in Bali Province During the Period (2017-2021) - Giovanni, Alveda Elian; Faridatussalam, Sitti Retno (Jurnal Ekonomi Balance, 2023)
This study aimed to break down the impact of the Human Development Index, Foreign Investment, Domestic Investment and Population Projections on Monetary Development in Bali Area During the 2017-2021 Period. By involving an example of information in 9 locale in Bali. The data used is secondary and multiple linear regression analysis is the method used. Economic growth is the dependent variable, while the human development index, foreign investment, domestic investment and population projection are independent variables. The results of the study indicate that economic growth is influenced by the human development index variable, but economic growth is not influenced by the variables of foreign investment, domestic investment and population projections have no effect on.